Perspektif Perkumpulan Profesi Pengelola Rekod Indonesia (P3RI) tentang Right to be Forgotten dalam Pelindungan Data Pribadi - Fachmi, Achmad; Rahmi, Rahmi; Cholil, Abdul (Direktorat Repositori, Multimedia, dan Penerbitan Ilmiah - Badan Riset dan Inovasi Nasional (BRIN Publishing), 2025)
This study highlights the importance of aligning the Right to be Forgotten (RtbF) with personal data protection (PDP) policies and emphasizes the need for further research on its practical implementation in records management. While RtbF represents a strategic step toward safeguarding digital privacy, its application remains challenging due to the need to balance individual rights with organizational obligations to retain records in compliance with regulations. Using a quantitative approach, data were collected through an online survey involving 66 Indonesian Records Management Professionals Association (P3RI) members and analyzed using SPSS with chi-square tests. The findings reveal that 90% of respondents acknowledge the importance of PDP, and 85% oppose data processing without consent. Furthermore, 48.5% support the implementation of RtbF in records management (mean score: 3.3182), 51.5% report difficulties in deleting data during retention periods, and 50% (mean score: 1.7727) doubt the feasibility of its implementation within organizations. This study offers an initial contribution to shaping policy direction and practical frameworks for RtbF implementation in the Indonesian archival context.